Do chimpanzees (Pan troglodytes) attribute preferences to virtual competitors? - Emilie Rapport Munro; Matthias Allritz; Kenneth Schweller; Daniel B. M. Haun; Josep Call (PLoS ONE, 2025)
Many animal species live in multi-level societies regulated by complex patterns of dominance. Avoiding competition with dominant group-mates for resources such as food and mates is an important skill for subordinate individuals in these societies, if they wish to evade harassment and aggression. Chimpanzees (Pan troglodytes) are an example of such a species. This study investigated whether chimpanzees could understand the food preferences of their competitors, and make use of this understanding to select non-contested food items. Fifteen chimpanzees were given thorough experience of the differing target preferences of two virtual competitors. In the test, subjects had to select which of the two targets to approach, based on which competitor was present. To choose correctly, they would have to integrate the competitors’ preferences from across disparate observations, and then infer, before the competitor acted, what they would do in a novel situation. We also included a control condition featuring two targets for which subjects had no information about the competitors’ potential biases. The chimpanzees rapidly learned to direct their virtual agent to collect the targets, and some responded with vocalizations and hard knocking against the screen when competitors “stole” targets from the agent the subject was guiding. However, statistical analyses showed that, both at the individual and the group level, they did not succeed in selecting the correct target item at above-chance levels. Additionally, there was no significant difference between their performance in the test and control. We identify theoretical and methodological discrepancies that could explain the contrasting results of this and other studies.